Antifungal evaluation of formulated ointment from sphenocentrum jollyanum root extract (2020)
In the light of high cost and frequent reoccurrence of current antifungal drugs, there is a need to explore the natural product resources in managing fungal infection, candidiasis, in which Candida albicans is the causative agent. This study is aimed at evaluating the in vitro and in vivo antifungal activity of Sphenocentrum jollyanum in view of the folkloric use in dressing chronic wounds. The ethylacetate fraction of 70% w/v methanol extract of S. jollyanum root (SJRME) was assessed for in vitro anticandidal activity using agar dilution method. Five groups of Candida albicans infected albino rats were treated with graded concentrations of ethylacetate fraction formulated ointment (50 - 200 mg/mL), with tioconazole cream 1% and normal saline as controls. Skin swabs were taken on days 0, 3, 6, 9 and 12 and placed on tryptone soya broth for three days. Serial dilution of the skin swabs was carried out and fungal loads determined using colony counter. The physical properties of the ointment formulated were evaluated. The ethylacetate fraction of SJRME was found to be active at tested concentrations against Candida albicans with a minimum inhibitory concentration of 12.5 mg/mL. Significant activity was also observed against other species of Candida and plant fungi. The formulated ointment had moderate viscosity, smooth texture, bland odour and bright yellow color. Treatment groups showed a significant reduction in fungal loads of skin swabs and ethylacetate fraction of SJRME possess antifungal activity and may therefore be potent templates in antifungal drug development.